Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera) VIII: One new species of Metriogryllacris (Metriogryllacris) amitarum Group from Guangxi - Yu, Lijiang; Liu, Hong; Bian, Xun (Zootaxa, 2022)
This paper describes one new species of Metriogryllacris (Metriogryllacris) amitarum group from Guangxi Huaping National Nature Reserve. A key to the species group is provided. The examined specimen is deposited in Guangxi Normal University.